Measurement of expansion coefficients of four steel types. (November 2013) - Xu, G.; Deng, P.; Wang, G. X.; Cao, L. F.; Liu, F.
Abstract : The expansion coefficients of four typical steel grades on hot continuous rolling mill were measured and analysed, and linear, average and instant expansion coefficients were derived. The main factors affecting dilation coefficients were analysed, and the influence of sampling direction on expansion coefficients was investigated. The results show that the effect of chemical composition on the coefficient of thermal expansion (CTE) is caused by the change of phase transformation points. It also indicates that the CTE is not affected by sampling direction, and the dilation amount of steels should be calculated by segmented regression models obtained on the basis of standard measurement. The results clarify some basic concepts on expansion coefficient of metal materials. The measured CTEs of four steel grades provide the basis for the accurate control of width of these steels.